Hubungan Antara Tingkat Pengetahuan dan Peran Keluarga dalam Upaya Pencegahan HIV/AIDS Pada Remaja di Wilayah Kerja Puskesmas Prabumulih Timur Tahun 2022 - Parmin, Selamat; Safitri, Serli Wulan (JURNAL KESEHATAN TERAPAN, 2023)
Acquired Immune Deficiency Syndrome (AIDS) is a collection of symptoms of immune system damage.HIV-AIDS is a global health problem in both developed and developing countries. The number of HIVAIDS cases in adolescents in Indonesia has increased. Knowledge of how HIV-AIDS is transmitted isvery important in efforts to prevent HIV-AIDS in adolescents. families in efforts to prevent HIV-AIDSin adolescents. The purpose of this study was to determine the relationship between the level ofknowledge and the role of the family with HIV-AIDS prevention efforts in adolescents at the EastPrabumulih Health Center. This research is quantitative by using a descriptive correlation design witha cross sectional approach. The sampling technique uses non-probability random sampling withaccidental sampling. The research location was in the East Prabumulih Health Center area on August20 - September 10 2022. The population in this study were all adolescents in the East PrabumulihHealth Center work area, both men and women aged 13-21 years and for a sample of 177 respondents.The results obtained based on the chi square test showed that there was a relationship between the levelof knowledge and efforts to prevent HIV-AIDS in adolescents with a P-value of 0.000, and there was arelationship between the role of the family and efforts to prevent HIV-AIDS in adolescents with a Pvalue of 0.001.